2006
DOI: 10.1167/iovs.05-0314
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Uveal Melanoma Reveals Novel Potential Markers Involved in Tumor Progression

Abstract: Tumor progression and development of metastases is a multicomplex system. Comparing protein expression in two cell lines derived from metastases with a cell line derived from a primary uveal melanoma from the same patient identified proteins involved in tumor progression, and proteins specifically expressed in the metastases, which have the potential of becoming clinically useful biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…Our study successfully identified 14 statistically significant differentially expressed proteins, as outlined in Table 2, from which four proteins (vimentin, beta-hexosaminidase subunit alpha, alpha-enolase, and 40S ribosomal protein SA) have been identified in the context of the metastatic phenotype of uveal melanoma in previous studies. 18,19,31 Our 2D DIGE analysis revealed a 2.2-fold up-regulation of FABP3 in uveal melanomas that did subsequently metastasize; this trend was confirmed by our immunohistochemical studies. FABP3 is a member of a multigene family including nine FABPs and the cellular retinoid binding proteins.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our study successfully identified 14 statistically significant differentially expressed proteins, as outlined in Table 2, from which four proteins (vimentin, beta-hexosaminidase subunit alpha, alpha-enolase, and 40S ribosomal protein SA) have been identified in the context of the metastatic phenotype of uveal melanoma in previous studies. 18,19,31 Our 2D DIGE analysis revealed a 2.2-fold up-regulation of FABP3 in uveal melanomas that did subsequently metastasize; this trend was confirmed by our immunohistochemical studies. FABP3 is a member of a multigene family including nine FABPs and the cellular retinoid binding proteins.…”
Section: Discussionsupporting
confidence: 71%
“…The majority of these studies use cell line models. 18,19 Zuidervaart et al 18 isolate and compare uveal melanoma cell lines derived from a primary tumor and from two of its liver metastases from the same patient. They identify 24 differentially expressed proteins; most of these have previously been reported to be involved in tumor metastasis.…”
Section: Purposementioning
confidence: 99%
“…Since tumor tissue is heterogeneous mixture of several cell types, cultured cell lines may be preferable for the screening of biomarkers. To search for biomarkers useful for the diagnosis of metastases, primary and metastatic cell lines were compared and several candidate biomarkers were successfully discovered (Table 4) (Bernard et al, 2003;Zuidervaart et al, 2006;Al-Ghoul et al, 2008). Proteomics analysis of melanoma-associated fibroblast stromal cells revealed the aberrant expression of several proteins not detected in normal fibroblasts (Paulitschke et al, 2009).…”
Section: Screening For Tumor Tissues and Cell Linesmentioning
confidence: 99%
“…They have been used for breast cancer [17,18], ovarian cancer [19], colorectal cancer [20], esophageal squamous cell carcinoma [21], uveal melanoma [22], urothelial cancer [23], prostate cancer [24], colon cancer [25], Alzheimer's disease [26], neurodegenerative diseases [27,28], brain disorders [29], liver toxicity [30], cystic fibrosis [31], amyotrophic lateral sclerosis and Parkinson's disease [32], and urological malignancies, bladder, and renal cancers [33]. These are by no means all the research articles published about the above diseases.…”
Section: Initial Considerationsmentioning
confidence: 99%